The Effects of Anthropogenic Heat Release on Urban Meteorology and Implication for Haze Pollution in the Beijing-Tianjin-Hebei Region - Ruiting Liu; Zhiwei Han (Advances in Meteorology)
In this study, the effect of anthropogenic heat release (AHR) on meteorological variables and atmospheric diffusion capability and implication for haze pollution in the Beijing-Tianjin-Hebei region in January 2013 were investigated by using Weather Research and Forecasting (WRF) model with an urban canopy model (UCM) and an AHR scheme. The comparison with observation demonstrated the WRF/UCM model taking AHR into account apparently improved meteorological prediction, especially for surface air temperature at 2 m (T2). The model also exhibited a better performance for planetary boundary layer (PBL) height. This study revealed that AHR from cities exerted a significant impact on meteorology by generally increasing surface air temperature and wind speed, decreasing relative humidity, and elevating PBL height and near surface turbulent kinetic energy (TKE), which could consequently reduce surface pollutant concentration and mitigate haze pollution by enhancing atmospheric instability and turbulent mixing and reducing aerosol hygroscopic growth.